IMPROVING STUDENTS’ ENGLISH READING SKILLS BY USING PROJECT- BASED LEARNING (PjBL) IN MUHAMMADIYAH UNIVERSITY OF BENGKULU - Saputra, Ilham; Purnawan, Ari; Angraini, Ria (Ridwan Institute, 2025)
The study aimed to determine the effectiveness of project-based learning (PjBL) in improving reading skills while identifying challenges associated with this approach. The research was conducted over two cycles during the second semester of the academic year 2023/2024, specifically from May 20 to July 10, 2024. The participants in the study consisted of 24 second-semester English students, including both male and female students. The qualitative data were gathered through observations and interviews, while quantitative data were obtained from reading assessments conducted before and after the intervention. The expected outcomes of the research included improved reading skills, increased student engagement in PjBL activities, and identification of challenges in the implementation of this approach, with the aim of enhancing the overall educational experience for students. It can be concluded that the use of Project-Based Learning significantly enhanced the students' reading skills in the Second Semester at Muhammadiyah University of Bengkulu within the English Education program.